2017
DOI: 10.1186/s12871-017-0332-4
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol vs dexmedetomidine for emergence agitation control in pediatric patients undergoing adenotonsillectomy with sevoflurane anesthesia: prospective randomized controlled clinical study

Abstract: BackgroundThis study was designed to compare the efficacy of an intraoperative single dose administration of tramadol and dexmedetomidine on hemodynamics and postoperative recovery profile including pain, sedation, emerge reactions in pediatric patients undergoing adenotonsillectomy with sevoflurane anesthesia.MethodsSeventy-seven patient, aged 2–12, undergoing adenotonsillectomy with sevoflurane anesthesia was enrolled in this study. Patients were randomly assigned to receive either intravenous 2 mg/kg tramad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…Only one study in this meta-analysis compared the effects of dexmedetomidine and tramadol; it found that both tramadol and dexmedetomidine were effective for controlling pain and the emergence of agitation. 18 Similarly, we also showed that post-operative pain and agitation were significantly lower in patients who received dexmedetomidine compared with tramadol. Based on these results, we conclude that dexmedetomidine provides more effective pain and agitation control than tramadol in paediatric patients who undergo adenotonsillectomy surgery using sevoflurane.…”
Section: Ta B L E 1 Comparison Of Baseline Characteristics Of Patientsupporting
confidence: 64%
See 1 more Smart Citation
“…Only one study in this meta-analysis compared the effects of dexmedetomidine and tramadol; it found that both tramadol and dexmedetomidine were effective for controlling pain and the emergence of agitation. 18 Similarly, we also showed that post-operative pain and agitation were significantly lower in patients who received dexmedetomidine compared with tramadol. Based on these results, we conclude that dexmedetomidine provides more effective pain and agitation control than tramadol in paediatric patients who undergo adenotonsillectomy surgery using sevoflurane.…”
Section: Ta B L E 1 Comparison Of Baseline Characteristics Of Patientsupporting
confidence: 64%
“…A subgroup analysis showed that dexmedetomidine decreased the severity and frequency of agitation more effectively than other opioids. Only one study in this meta‐analysis compared the effects of dexmedetomidine and tramadol; it found that both tramadol and dexmedetomidine were effective for controlling pain and the emergence of agitation . Similarly, we also showed that post‐operative pain and agitation were significantly lower in patients who received dexmedetomidine compared with tramadol.…”
Section: Discussionmentioning
confidence: 70%
“…Although the sedative effect of dexmedetomidine could cause the residual sedation, dexmedetomidine would not influence the duration of staying PACU, regardless of the administration method. For these results, we could consider several points.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies with 1,552 participants were included for the meta-analysis, and the results of the study characteristics were described in Table I. Outcomes for analysis were postoperative pain (pain scores) in the postanesthesia care unit (PACU), [10][11][12][13][14][15][16][17][18] postoperative analgesic requirements (doses of postoperative opioids or nonopioid analgesics), 4,8,[10][11][12]16,17,[19][20][21][22][23][24][25][26][27][28][29][30] postoperative agitation (agitation scores and incidence during recovery), 8,10,11,13,[15][16][17][18][19][21][22][23]31 desaturation, 8,10,15,17,18,20,…”
Section: Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…However, numerous studies have demonstrated that sevoflurane anesthesia in patients had a higher risk of postoperative agitation, particularly in children (8,9). The incidence rate of EA varies depending on the type and severity of EA.…”
Section: Introductionmentioning
confidence: 99%